Non-regular quadratic stochastic operators with countable state space - Ganikhodjaev, Nasir; Anorov, Obidion; Chin, Hee Pah (Penerbit Universiti Kebangsaan Malaysia, 2024)
In this paper we present an example of non-regular extremal Volterra quadratic stochastic operator defined on infinite-dimensional simplex. We show that the construction of this operator to odd dimensional face of infinite-dimensional simplex is non-regular transformation. We employ method of approximation to prove non-regularity of initial operator.